THE FEBRUARY REVOLUTION OF 1917 AND SERBIA - A. Yu. Timofeev (Vestnik MGIMO-Universiteta)
The paper considers the Serbian-Russian official relations on the eve and during the February Revolution of 1917 in Russia. The study is based on numerous archival sources and on the wide range of Russian and Serbian historiography. For the best understanding of changes of Russian foreign policy on the Balkans caused by the Provisional Government’s coming to power the author investigates the Russian Empire plans of post-war reorganization of the western part of the Balkan Peninsula; the influence of other countries – allies of Russia in World War I is also analyzed. The Serbian official representatives noted the English influence on the coup in Russia though they did not provide any exact data about it. The official representatives of Serbia were not unanimous in their reactions towards the February revolution. The military took a cautious approach and noted the growth of negative phenomena, their opinions were rather conservative. Diplomats were more liberal in their assessments, they criticized the fallen dynasty more strongly and showed greater optimism than the military. At the same time all of them were unanimous in the necessity to follow the path of full neutrality and non-interference in internal affairs of Russia. The author comes to the conclusion that despite the radical changes that the February revolution made in the post-war reconstruction of the Balkan Peninsula, Serbia could not have foreseen those changes beforehand. The exceptions were only some analytical works of the officers of the Serbian General Staff.